The age structure transition and the demographic dividend: An opportunity for rapid economic take-off in Sri Lanka - de Silva, W. Indralal (My University, 2012)
During the past few decades the total size and the age structure of the Sri Lankan population have been subjected to irreversible changes. This paper using population data is an attempt to identify the manner in which age structure transition affects the economic development in Sri Lanka. The age structure transition in Sri Lanka has produced a demographic dividend, ranging from year 1991 to 2017, which is conducive for an economic takeoff. During this period, the proportion of the working age population, aged 15 - 59 years, is significantly larger than the proportion of the dependents. The dividend will not last long since the elderly dependency is increasing rapidly. Therefore, this is an opportunity that needs to be used immediately. If this opportunity is missed out, the policy makers will have to address the consequences of demographic turbulence - an increasing dependency, which would depress the economic development. Mere existence of the dividend would be ineffective without a proper environment for economic acceleration. Nevertheless, in a congenial environment of political stability, adequate savings, investment potential, human capital, productivity and the knowledge economy, the optimum utilization of the dividend to gain economic acceleration would materialize.
Keywords: Age Structure Transition - Demographic Dividend - Dependency - Economic Development